2015
DOI: 10.1007/s10585-015-9752-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-metastatic action of FAK inhibitor OXA-11 in combination with VEGFR-2 signaling blockade in pancreatic neuroendocrine tumors

Abstract: The present study sought to determine the anti-tumor effects of OXA-11, a potent, novel small-molecule amino pyrimidine inhibitor (1.2 pM biochemical IC50) of focal adhesion kinase (FAK). In studies of cancer cell lines, OXA-11 inhibited FAK phosphorylation at phospho-tyrosine 397 with a mechanistic IC50 of 1 nM in TOV21G tumor cells, which translated into functional suppression of proliferation in 3-dimensional culture with an EC50 of 9 nM. Studies of OXA-11 activity in TOV21G tumor-cell xenografts in mice re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Since certain FAK inhibitors demonstrated a synergistic effect with cisplatin in other malignant diseases [9], cell viability was also measured when BI 853520 was applied in combination with cisplatin. In these experiments, we used the relatively sensitive and merlin-negative P31 and the more resistant and merlin-expressing SPC212 cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Since certain FAK inhibitors demonstrated a synergistic effect with cisplatin in other malignant diseases [9], cell viability was also measured when BI 853520 was applied in combination with cisplatin. In these experiments, we used the relatively sensitive and merlin-negative P31 and the more resistant and merlin-expressing SPC212 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The promising results from trials using first-line bevacizumab, cisplatin, and pemetrexed combinations in MPM patients underline the importance of anti-angiogenic therapies in this particular malignancy [45]. Importantly, FAK as a downstream element integrates proangiogenic signals received both via VEGFRs and integrin receptors, and as such, it might further increase the efficacy of VEGFR-directed therapeutic modalities [9, 46]. For example, in vivo studies in pancreatic neuroendocrine tumors indicated reduced incidence and number and size of liver metastases following the combination of another FAK inhibitor (OXA-11) with VEGFR2 blockade [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations